2007
DOI: 10.1161/01.atv.0000253502.83167.31
|View full text |Cite
|
Sign up to set email alerts
|

A Causal Role for Endothelin-1 in the Vascular Adaptation to Skeletal Muscle Deconditioning in Spinal Cord injury

Abstract: Objective-Endothelin-1 (ET-1) contributes to the increased peripheral resistance in heart failure and hypertension.Physical inactivity is associated with cardiovascular disease and characterized by increased vascular tone. In this study, we assess the contribution of ET-1 to the increased vascular tone in the extremely deconditioned legs of spinal cord-injured (SCI) individuals before and after exercise training. Methods and Results-In 8 controls and 8 SCI individuals, bilateral thigh blood flow was measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…Exercise-induced increases in blood flow and, thus, shear stress to the artery wall is a likely mechanism by which physical activity exerts an insulin-sensitizing effect on the aorta and a decrease in ET-1 (24,44). This hypothesis is supported by evidence that 1) shear stress reduces expression of ET-1 in cultured endothelial cells (59), 2) removal of WR for 7 days increases expression of ET-1 in the rat iliac artery (41), 3) rat soleus muscle feed arteries, known to be chronically exposed to high levels of blood flow, display greater insulin-stimulated dilation, as a result of reduced ET-1 activation, than gastrocnemius feed arteries, known to be chronically exposed to lower levels of flow (26), and 4) inactive lower limbs of spinal cord injury patients, chronically exposed to low blood flow and shear stress (3), exhibit an enhanced ET-1-mediated basal vascular tone (58).…”
Section: Discussionmentioning
confidence: 99%
“…Exercise-induced increases in blood flow and, thus, shear stress to the artery wall is a likely mechanism by which physical activity exerts an insulin-sensitizing effect on the aorta and a decrease in ET-1 (24,44). This hypothesis is supported by evidence that 1) shear stress reduces expression of ET-1 in cultured endothelial cells (59), 2) removal of WR for 7 days increases expression of ET-1 in the rat iliac artery (41), 3) rat soleus muscle feed arteries, known to be chronically exposed to high levels of blood flow, display greater insulin-stimulated dilation, as a result of reduced ET-1 activation, than gastrocnemius feed arteries, known to be chronically exposed to lower levels of flow (26), and 4) inactive lower limbs of spinal cord injury patients, chronically exposed to low blood flow and shear stress (3), exhibit an enhanced ET-1-mediated basal vascular tone (58).…”
Section: Discussionmentioning
confidence: 99%
“…Although a reduction in leg vascular resistance in individuals with SCI has been reported in one study, 83 the majority of studies report the opposite, that is, leg vascular resistance, measured during supine rest, is increased following SCI. 35,[84][85][86] The mechanism(s) responsible for the increased leg vascular resistance do not appear to be related to loss of centrally mediated sympathetic tonic control, as graded infusions of phentalomine (competitive antagonist of a-adrenoceptors) during b-adrenoceptor blockade induced a similar degree of upper-leg vasodilation in SCI compared with AB, indicating that a-adrenergic tone is relatively well preserved in the legs of individuals with SCI. 84 Instead, increased vascular resistance may be accounted for by alterations in vasoconstrictor pathways.…”
Section: Functional Adaptationsmentioning
confidence: 99%
“…88 Although such hypersensitivity may be explained partly by an impairment of the arterial baroreflex, 88 it still remains unclear in humans whether the enhanced pressor response actually results from post-synaptic hypersensitivity, as impaired re-uptake of NE may also account for such a response. There is also growing evidence that other vasoconstrictor pathways, such as angiotensin II 88,91 and endothelin I, 85 may also contribute to the increased vascular resistance in the lower limbs of individuals with SCI.…”
Section: Functional Adaptationsmentioning
confidence: 99%
“…The significance of physical inactivity as a key determinant of the contribution of ET-1 to vascular tone is recently supported by another human in vivo study, which demonstrated that the contribution of ET-1 to baseline leg vascular tone in the extremely inactive legs of individuals with spinal cord injury is markedly increased (through ET A receptors). 12 The link with physical inactivity is supported by the largely reversed ET-1-mediated vasoconstriction in these subjects after 6 weeks of exercise training. Taken together, the results of both of these studies suggest that physical inactivity plays a major role in the ET-1-mediated vascular tone in humans through an ET A receptor-dependent mechanism.…”
mentioning
confidence: 89%
“…4,13 This role is supported by short-term (hours to weeks) beneficial effects of selective and/or dual ET A/B receptor antagonists. However, the identification of physical inactivity as a major determinant of the ET-1 pathway 9,12 emphasizes that inactivity, rather than the pathology of these specific cardiovascular diseases, may be a strong candidate to explain the ET-1-mediated elevated vascular tone in cardiovascular disease, which may be substantially reversible by training.…”
mentioning
confidence: 99%